FACTORS AFFECTING THE PURCHASE PRICE OF GAYO ARABICA COFFEE BEANS (CASE STUDY OF BAITUL QIRADH BABURRAYAN COOPERATIVE) - Mulya Rizka; Devi Agustia (RADJA PUBLIKA, 2023)
The purpose of this study was to determine the factors that influence the purchase price of Gayo Arabica coffee beans in the Baitul Qiradh Baburrayan Cooperative. The data used in this research is secondary data. The analytical method used in this study is quantitative analysis using SPSS version 25 and using an analytical model using multiple linear regression analysis. The results of research data processing show a correlation coefficient (R) of 0.898, this means that the variables of purchase quantity, moisture content, and trace content have a very strong relationship of 89.8 percent and have a significant effect on the purchase price of coffee together. By partial test in this study the variables that have a significant effect on the purchase price are the moisture content and trace levels.